PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL DAN PERILAKU BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI (STUDI PADA MAHASISWA AKUNTANSI SYARIAH UNIVERSITAS ISLAM NEGERI SALATIGA) - Nur Isnaini; Dwi Muryani; Nur Kabib (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2024)
Through emotional intelligence, intellectual intelligence, and learning behavior, individuals can improve their understanding of accounting. Currently, with formal education on emotional intelligence and intellectual intelligence, it is expected that students can develop their ability to understand accounting concepts. Therefore, with a deep understanding of accounting, this encourages an increase in the quality of analysis and evaluation which can ultimately improve the efficiency of decision making and management of financial information. The purpose of this study was to determine whether there is an effect of emotional intelligence, intellectual intelligence, and learning behavior on the level of accounting understanding. This type of research uses quantitative methods with a sample of 127 respondents. The source of data obtained in this study was from distributing questionnaires. The update in this study is the addition of intellectual intelligence variables and the use of multiple intelligence theory and attribution theory. While the data analysis technique used in this study uses multiple linear regression analysis. The results of this study indicate that emotional intelligence has a positive and insignificant effect on the level of accounting understanding. Intellectual intelligence and learning behavior have a positive and significant effect on the level of accounting understanding.